Ultrastructural Adaptation of the Cardiomyocyte to Chronic Mitral Regurgitation - Corporan, Daniella; Segura, Ana; Padala, Muralidhar (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Mitral regurgitation (MR) imposes volume overload on the left ventricle (LV) and elevates wall stress, triggering its adverse remodeling. Pronounced LV dilation, minimal wall thinning, and a gradual decline in cardiac ejection fraction (EF) are observed. The structural changes in the myocardium that define these gross, organ level remodeling are not known. Cardiomyocyte elongation and slippage have both been hypothesized, but neither are confirmed, nor are the changes to the cardiomyocyte structure known. Using a rodent model of MR, we used immunohistochemistry and transmission electron microscopy (TEM) to describe the ultrastructural remodeling of the cardiomyocyte. Methods: Twenty-four male Sprague-Dawley rats (350–400 g) were assigned to two groups: group (1) rats induced with severe MR (n = 18) and group (2) control rats that were healthy and age and weight matched (n = 6). MR was induced in the beating heart using a 23-G ultrasound-guided, transapical needle to perforate the anterior mitral leaflet, and the rats were followed to 2, 10, and 20 weeks (n = 6/time-point). Echocardiography was performed to quantify MR severity and to measure LV volume and function at each time-point. Explanted myocardial tissue were examined with TEM and immunohistochemistry to investigate the ultrastructural changes. Results: MR induced rapid and significant increase in end-diastolic volume (EDV), with a 50% increase by 2 weeks, compared with control. Rise in end-systolic volume (ESV) was more gradual; however, by 20 weeks, both EDV and ESV in MR rats were increased by 126% compared with control. A significant decline in EF was measured at 10 weeks of MR. At the ultrastructural level, as early as 2 weeks after MR, cardiomyocyte elongation and increase in cross-sectional area were observed. TEM depicted sarcomere shortening, with loss of Z-line and I-band. Desmin, a cytoskeletal protein that is uniformly distributed along the length of the cardiomyocyte, was disorganized and localized to the intercalated disc, in the rats induced with MR and not in the controls. In the rats with MR, the linear registry of the mitochondrial arrangement along the sarcomeres was lost, with mitochondrial fragmentation, aggregation around the nucleus, and irregularities in the cristae. Discussion: In the setting of chronic mitral regurgitation, LV dilatation occured by cardiomyocyte elongation, which manifests at the subcellular level as distinct ultrastructural alterations of the sarcomere, cytoskeleton, and mitochondria. Since the cytoskeleton not only provides tensegrity but has functional consequences on myocyte function, further investigation into the impact of cytoskeletal remodeling on progressive heart failure or recovery of function upon correcting the valve lesion are needed.